DNA polymerases in the risk and prognosis of colorectal and pancreatic cancers. (24th October 2019) - Silvestri, Roberto; Landi, Stefano
Abstract: Human cancers arise from the alteration of genes involved in important pathways that mainly affect cell growth and proliferation. DNA replication and DNA damages recognition and repair are among these pathways and DNA polymerases that take part in these processes are frequently involved in cancer onset and progression. For example, damaging alterations within the proofreading domain of replicative polymerases, often reported in patients affected by colorectal cancer (CRC), are considered risk factors and drivers of carcinogenesis as they can lead to the accumulation of several mutations throughout the genome. Thus, replicative polymerases can be involved in cancer when losses of their physiological functions occur. On the contrary, reparative polymerases are often involved in cancer precisely because of their physiological role. In fact, their ability to repair and bypass DNA damages, which confers genome stability, can also counteract the effect of most anticancer drugs. In addition, the altered expression can characterise some type of cancers, which exacerbates this aspect. For example, all of the DNA polymerases involved a damage bypass mechanism, known as translesion synthesis, with the only exception of polymerase theta, are downregulated in CRC. Conversely, in pancreatic ductal adenocarcinoma (PDAC), most of these polymerase result upregulated. This suggests that different types of cancer can rely on different reparative polymerases to acquire drug resistance. Here we will examine all of the aspects that link DNA polymerases with CRC and PDAC.